SYSTEMATIC LITERATURE REVIEW: Pembelajaran Project Based Learning (PjBL) Terhadap Kemampuan Literasi Matematika Siswa - Reni Roikhatul Jannah; St. Budi Waluya; Mohammad Asikin; Zaenuri (Civiliza Publishing, 2021)
Mathematical literacy is an important factor in the learning process. Mathematical literacy is able to help students succeed in their lives, because mathematics is not just a science but the mastery of mathematical skills by understanding the mathematics around it. PISA results of Indonesian students occupy mathematical literacy at levels 1 and 2 of 6 levels, which shows students are only able to solve routine problems. One of the steps so that students can develop mathematical literacy skills is project-based learning (PjBL), students are more active in learning by exploring, interpreting, synthesizing, and providing information in completing a project. The type of research method used is Systematic Literature Review (SLR) Several studies of articles on mathematical literacy, weak mathematical literacy in the content of change and relationship, quantity and uncertainty and data show that students are less able to understand teaching materials related to arithmetic functions, algebra, number concepts, statistics and probability. The development of students' mathematical literacy skills with the tendency of intelligence possessed by students can also affect the learning styles used by students.Besides this, Project Based Learning (PjBL) learning is suitable learning in improving mathematical literacy skills. fish. Students not only learn in theory but students also learn practically in real life.